2022
DOI: 10.1051/e3sconf/202236103005
|View full text |Cite
|
Sign up to set email alerts
|

Criteria of pesticide selection in shallot pestdisease control in Brebes Regency, Central Java

Abstract: Farmers’ socio-economics, beliefs, perceptions, and attitudes affect their behavior toward pesticides. This study was aimed at identifying criteria considered by shallot farmers in selecting and using pesticides. A survey of shallot pesticide-use was carried out in Brebes, Central Java. Data were collected by interviewing 75 respondents that was proportiona-tely and randomly selected from three villages in Brebes. By using factor analysis, four components are extracted and they account for 65.15% of the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Insecticides and fungicides were the most common pesticides found in the respondents' houses since the farmers chose pesticides that could kill the most attacking pests, such as insects and fungi. These findings are consistent with other research findings that found the same types and groups of pesticides (14)(15).…”
Section: Transportation and Fate Of Pesticides From The Shallot Farmsupporting
confidence: 93%
See 1 more Smart Citation
“…Insecticides and fungicides were the most common pesticides found in the respondents' houses since the farmers chose pesticides that could kill the most attacking pests, such as insects and fungi. These findings are consistent with other research findings that found the same types and groups of pesticides (14)(15).…”
Section: Transportation and Fate Of Pesticides From The Shallot Farmsupporting
confidence: 93%
“…were also found in other areas of shallot farming such as Kalimantan (16). Meanwhile, insecticides were used to control shallot pests such as Spodoptera exigua, Spodoptera litura, and Thrips tabaci (15). The aforementioned insects and fungi grow well in the tropics.…”
Section: Insecticides and Fungicides At The Respondents' Housesmentioning
confidence: 99%